PLATFORMIZATION OF CULTURAL PRODUCTION ON YOUTUBE: CASE STUDY OF 2QUADRINHOS CHANNEL - Montardo, Sandra Portella (2023)
This paper seeks to investigate the platformization of cultural production of the 2quadrinhos YouTube channel through an analysis of practices and affordances. In a scenario in which cultural producers are increasingly dependent on the technological, business and governance infrastructure of digital platforms, when creating content, the question arises in what way this issue emerges in a You Tube channel about comics. The research used a case study, a bibliographic and documental survey and a semi-structured interview. As a result, editorial guidelines were identified that dynamically articulate content curation on comic books and datafication strategies proposed by You Tube.